Is it enough to be willing to win or do you have to be smart? The relationship between competitive worldviews, cognitive abilities, and applicant faking in personality tests. (15th July 2020) - Schilling, Michael; Sparfeldt, Jörn R.; Becker, Nicolas; Engel, Marie; Levacher, Julie; Sebastian, Tilman F. P.; Schäfer, Juliane; Schwabe, Sarah; König, Cornelius J.
Abstract: Recent research has highlighted competitive worldviews as a key predictor of faking—the intentional distortion of answers by candidates in the selection context. According to theoretical assumptions, applicants' abilities, and especially their cognitive abilities, should influence whether faking motivation, triggered by competitive worldviews, can be turned into successful faking behavior. Therefore, we examined the influence of competitive worldviews on faking in personality tests and investigated a possible moderation of this relationship by cognitive abilities in three independent high school and university student samples ( N 1  = 133, N 2  = 137, N 3  = 268). Our data showed neither an influence of the two variables nor of their interaction on faking behavior. We discuss possible reasons for these findings and give suggestions for further research.